Nutrient sink limitation constrains growth in two barley species with contrasting growth strategies - Burnett, Angela C. (Plant Direct, 2018)
Mineral nutrients exert important limitations on plant growth. Growth is limited by the nutrient source when it is constrained by nutrient availability and uptake, which may simultaneously limit investment in photosynthetic proteins, leading to carbon source limitation. However, growth may also be limited by nutrient utilization in sink tissue. The relative importance of these processes is contested, with crop and vegetation models typically assuming source limitations of carbon and mineral nutrients (especially nitrogen). This study compared the importance of source and sink limitation on growth in a slower‐growing wild perennial barley (Hordeum bulbosum) and a faster‐growing domesticated annual barley (Hordeum vulgare), by applying a mineral nutrient treatment and measuring nitrogen uptake, growth, allocation, and carbon partitioning. We found that nitrogen uptake, growth, tillering, shoot allocation, and nitrogen storage were restricted by low nutrient treatments. Multiple lines of evidence suggest that low nutrient levels do not limit growth via carbon acquisition: (a) Carbohydrate storage does not increase at high nutrient levels. (b) Ratio of free amino acids to sucrose increases at high nutrient levels. (c) Shoot allocation increases at high nutrient levels. These data indicate that barley productivity is limited by the capacity for nutrient use in growth. Models must explicitly account for sink processes in order to properly simulate this mineral nutrient limitation of growth.